Minor and Crime: How the Law Applied for Juvenile? - Parhusip, Iin Geraldina Jalisna (Law Research Review Quarterly, 2021)
Criminality is all forms of speech, behavior and behavior that harm society and attack the safety of citizens, both those covered by law and those not yet covered by the criminal law. In carrying out the guidance and protection of children need the role of society through institutions and organizations. Children are part of the young generation as one of the human resources that is the potential and successor of the ideals of the nation's struggle in the future. They have a strategic role and are of special character and require coaching and protection for balanced, physical, mental and social growth and development. The handling of criminal cases with child offenders needs special attention, starting from the criminal law applicable to children. Handling of children as perpetrators of criminal acts every year always reap a good criticism from the community, this is due to the culture maintained from generation to generation of law enforcement mindset in handling the perpetrators of criminal acts.